Pengembangan Awal Alat Ukur Stres: Studi Kasus Pada Mahasiswa Universitas Malikussaleh - Fahtia fahtia (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2019)
This study aims to create a measuring tool to measure the scale of one's stress generated due to internet addiction. The method used in this study is a quantitative method with random sampling techniques. The main respondents of this study are active students range ranging from 18 to 26 years old and own a smartphone. The study collected a total of respondents. The data was analyzed by using IBM SPSS version 22. The result showed that the scale was valid (α : 0,9) indicating that the measure can be used to examine stress on stress of students due to internet addiction.